Elderly Tahsin Recitation of Al-Qur'an: Efforts to Eliminate Al-Qur'an Illiteracy - Arlina; Enny Nazrah Pulungan; Nurul Afdina Siregar (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2022)
The tahsin recitation of the Qur'an is an endeavour at Ma'had Abu Ubaidah bin al-Jarrah Medan to eradicate Qur'an illiteracy among the elderly. The activity is in reaction to Indonesia's high degree of Al-Qur'an illiteracy. This study gathered information from key informants and program administrators through a participatory observation approach. Data from the field suggest that senior participants are divided into groups based on their age before participating in a series of Al-Qur'an reading practices with examples of lip motions. Ma'had also offers e-learning services in order to improve learning outcomes. The eradication of Al-Qur'an illiteracy is a response to past socioeconomic conditions that prohibited people from learning to read the Al-Qur'an. These factors may include low economic levels, an unsupportive social context, and a lack of educational understanding.